ENHANCING STUDENTS CRITICAL READING SKILLS IN TEACHING ARGUMENTATIVE ESSAY - Richard Manuputty (Jurusan Pendidikan Bahasa dan Seni FKIP Universitas Pattimura, 2022)
Stereotypically, the teaching of writing is separated from reading subjects. As the results, many students are found to be passive and not critical in writing. This action research looks into the effectiveness of enhancing students’ critical reading in writing argumentative essays. It is investigating whether the genre-based cognitive reading and approach applied brings significant impacts in students’ writing ability? The results of the study indicated some moderate changes in writing argumentative skills which were analyzed and assessed through content analysis over two complete writing products submitted after two complete learning cycles. Some students of (N=18) are at developing learning stage of becoming critical in writing but not yet fluently in making strong arguments for their opinions. Some have already shown capability to organize their thoughts better in thesis writing but not successfully developed them with facts from their own factual experiences in supporting and defending their stands and arguments in development writing stage. The instructional learning system is found to be effective though obviously much time is needed for comprehending texts, and more writing practice is required before students can eventually perform better argumentative essays